Large-scale solar PV LCOE comprehensive breakdown methodology - Castillo- Ramírez, Alejandro; Mejía- Giraldo, Diego; Muñoz- Galeano, Nicolás (CT&F - Ciencia, Tecnología y Futuro, 2017)
This paper presents a breakdown cost methodology to evaluate Levelized Costs of Electricity for large-scale Photovoltaic (PV) plants. The breakdown is based on a comprehensive taxonomy to evaluate Investment Costs (IC) and Operation and Maintenance (O&M) expenditures. We added an IC disaggregation level, called elements, on top of the five-component breakdown of the Energy Information Administration (EIA). In addition, a novel structure for disaggregating O&M costs is also proposed. The methodology is evaluated over a 20-MW and a 150-MW PV power plant hypothetically placed in the municipality of Uribia (Guajira Colombia). Also deterministic sensitivity analysis based on discount rate (WACC, Weighted Average Capital Cost), energy generated, O&M costs and IC is performed to aid investors in their decisions.